Risk of Alzheimer's disease and related dementia by sex and race/ethnicity: The Multiethnic Cohort Study. Issue 9 (9th December 2021) - Lim, Unhee; Wang, Songren; Park, Song‐Yi; Bogumil, David; Wu, Anna H.; Cheng, Iona; Haiman, Christopher A.; Le Marchand, Loïc; Wilkens, Lynne R.; White, Lon; Setiawan, V. Wendy
Abstract: Introduction: Data are limited for comparison of sex‐ and race/ethnicity‐specific risks of Alzheimer's disease and related dementia (ADRD). Methods: In the population‐based Multiethnic Cohort, we estimated the age‐standardized diagnostic incidence rate (ASDIR) and relative risk of late‐onset ADRD ( n  = 16, 410) among 105, 796 participants based on Medicare claims (1999‐2014) by sex and race/ethnicity. Results: The ASDIR for ADRD was higher for women (17.0 per 1000 person‐years) than for men (15.3) and varied across African Americans (22.9 in women, 21.5 in men), Native Hawaiians (19.3, 19.4), Latinos (16.8, 14.7), Whites (16.4, 15.5), Japanese Americans (14.8, 13.8), and Filipinos (12.5, 9.7). Similar risk patterns were observed for AD. Adjustment for education and cardiometabolic diseases attenuated the differences. Accounting for deaths from competing causes increased the sex difference, while reducing the racial/ethnic differences. Less racial/ethnic disparity was detected among apolipoprotein E ( APOE ) e4 carriers. Discussion: More research is needed to understand the sex and racial/ethnic differences in ADRD.